The evolution of conifolds - Butcher, Neil A.; Saffin, Paul M. (Springer, 2008)
We simulate the gravitational dynamics of the conifold geometries (resolved and deformed) involved in the description of certain compact spacetimes. As the cycles of the conifold collapse towards a singular geometry we find that a horizon develops, shielding the external spacetime from the curvature singularity of the newly formed black hole. The structure of the black hole is examined for a range of initial conditions, and we find a candidate black-hole solution for the final state of the collapse.